2015
DOI: 10.1130/b31243.1
|View full text |Cite
|
Sign up to set email alerts
|

From the source area to the deposit: Collapse, fragmentation, and propagation of the Frank Slide

Abstract: The combination of structural data from the source area and descriptive data from the deposit's carapace, as well as remote sensing and statistical analysis, allows a better understanding of the collapse, fragmentation, and propagation processes of the Frank Slide rock avalanche. The in situ observed conservation of the stratigraphic sequence of the Turtle Mountain anticline's normal limb in the deposit is interpreted as the consequence of the collapse mode, involving simple shearing of the mass accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…The non-volcanic deposit of Blackhawk (California, USA) also presents similar features (Shea and van Wyk de Vries, 2008) ( Fig. 1a), as does the Frank Slide in Alberta (Canada) Hugr, 1986, 2011;Charrière et al, 2015). Features perpendicular to the flow direction are mainly present in the distal part of the deposit and are interpreted as the surface expression of the underneath topography.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The non-volcanic deposit of Blackhawk (California, USA) also presents similar features (Shea and van Wyk de Vries, 2008) ( Fig. 1a), as does the Frank Slide in Alberta (Canada) Hugr, 1986, 2011;Charrière et al, 2015). Features perpendicular to the flow direction are mainly present in the distal part of the deposit and are interpreted as the surface expression of the underneath topography.…”
Section: Introductionmentioning
confidence: 76%
“…In order to extend the proposed workflow to a real case study, we decided to apply the filtering gradient operator techniques to the well-known Frank Slide event (Alberta, Canada). This deposit presents several geometrical features, which are mainly longitudinal and perpendicular to the flow direction (Longchamp et al, 2011;Charrière et al, 2015). in this figure: inverse faults, normal faults, and strikeslip faults.…”
Section: (C) Comparison With Real Casementioning
confidence: 99%
“…They performed several laboratory tests using different block assemblages and their findings for the amount of fragmentation showed consistency with use of Hardin (1985) breakage parameters for the definition of how much fragmentation has taken place during a breakage event related with the total runout of the rock mass. Charrière et al (2015) also presented a model to calculate the successive block size distribution after fragmentation during a rock slide, which describes the breaking of a cubic block into two fragments with a random volume ratio, and in their turn their successive breaking in two more fragments each, for a chosen number of cycles. Further work is needed to develop transition models from the IBSD to the RBSD for fragmental rockfalls.…”
Section: Obtaining the Bsd From The Ibsdmentioning
confidence: 99%
“…Manzella (2008) conducted a series of laboratory experiments consisting of unconstrained flows of small rectangular blocks and gravel down an inclined slab, showing that the tests with bricks piled in an orderly arrangement in the source container have higher velocities and travel farther than those with bricks piled randomly and with loose gravel mass. Comparing the block size distributions of the source area and deposit surface of the Frank Slide, Charrière et al (2016) found that preexisting joint sets can exert primary control over the fragmentation processes, at least in the top layer of deposits. Ruiz‐Carulla et al (2017) proposed a three‐parameter rockfall fractal fragmentation model to predict the transformation of the in situ block size distribution to the resultant rockfall block size distribution.…”
Section: Introductionmentioning
confidence: 99%